2010
DOI: 10.2519/jospt.2010.3279
|View full text |Cite
|
Sign up to set email alerts
|

Plasticity of Muscle Architecture After Supraspinatus Tears

Abstract: Study Design Controlled Laboratory Study Objectives To measure the architectural properties of rat supraspinatus muscle after a complete detachment of its distal tendon. Methods Supraspinatus muscles were released from the left humerus of 29 rats (Sprague-Dawley, mass 400 - 450 g) and animals were returned to cage activity for 2 weeks (n = 12), 4 weeks (n = 9), or 9 weeks (n=8) before euthanasia. Measurements of muscle mass, pennation angle, fiber bundle length (sarcomere number), and sarcomere length perm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
49
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(51 citation statements)
references
References 31 publications
1
49
0
1
Order By: Relevance
“…Also, architectural parameters such as physiological cross-sectional area and normalized muscle fiber length (serial sarcomere number) can predict muscle maximal force, excursion, and velocity, which is particularly important for physical therapists. 72 Thus, as an evidence-based outcome measure, the sonographic assessment of cross-sectional supraspinatus tendon thickness was used because significant functional improvement may be related to structural changes of the tendon. 18,63,73 The finding of this study pointed out that not only the manual therapy intervention but also the kinesiotape intervention with exercise had no effect on tendon structure within 6 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…Also, architectural parameters such as physiological cross-sectional area and normalized muscle fiber length (serial sarcomere number) can predict muscle maximal force, excursion, and velocity, which is particularly important for physical therapists. 72 Thus, as an evidence-based outcome measure, the sonographic assessment of cross-sectional supraspinatus tendon thickness was used because significant functional improvement may be related to structural changes of the tendon. 18,63,73 The finding of this study pointed out that not only the manual therapy intervention but also the kinesiotape intervention with exercise had no effect on tendon structure within 6 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…17,18,39 Studies in rat, 14,15 sheep, 6,13 dog, 39 and human rotator cuff 7 have demonstrated that the muscle-tendon unit becomes retracted and stiffer after injury, which is attributed to changes in the muscle's structure. 6,[13][14][15]39 Specifically, as the muscle atrophies following tendon injury, it undergoes sarcopenia, 45 decreased muscle volume, 2,29,39 fibrofatty infiltration, 2,29,30,39 decreased capillary density, 6,13,20,39 and muscle fiber-type switching. 2 In some instances, full excursion of the injured muscle-tendon unit back to its anatomical footprint on the humeral head is not possible during surgical repair of torn rotator cuffs.…”
Section: Introductionmentioning
confidence: 99%
“…The unloading of tensile forces results in radial and longitudinal atrophy of the muscle. 47 Ultrastructural changes include myofibril disorganization with decreased sarcomere numbers and lengths. 3,29 A reduction in muscle mass and volume occurs after myofibril dissolution and degeneration.…”
mentioning
confidence: 99%